Crystal structure of 4,4′-dinitro-[1,1′-biphenyl]-2-amine - Md. Serajul Haque Faizi; Ashanul Haque; Necmi Dege; Syed Imran Hasan; Mustafa Dege; Valentina A. Kalibabchuk (Acta Crystallographica Section E: Crystallographic Communications, 2017)
In the title biphenyl derivative, C12H9N3O4, the dihedral angle between the benzene rings is 52.84 (10)°. The nitro group attached to the benzene ring is inclined to the ring by 4.03 (2)°, while the nitro group attached to the amino-substituted benzene ring is inclined to the ring by 8.84 (2)°. In the crystal, molecules are linked by two pairs of N—H...O hydrogen bonds, forming chains propagating along [101]. Within the chains, these N—H...O hydrogen bonds result in the formation of R22(20) and R22(14) ring motifs. The latter ring motif is reinforced by a pair of C—H...O hydrogen bonds, enclosing R21(6) ring motifs. The chains are linked by a second C—H...O hydrogen bond, forming a three-dimensional supramolecular structure.